Reversion to the Racial Mean and Mortgate Discrimination - Tino Sanandaji (Research Institute of Industrial Economics (IFN), 2009)
Studies of mortgage approvals find that minority borrowers are more likely to be denied loans, even when background variables such as current-year income are held constant. This article demonstrates that relying on current year income when comparing racial outcomes leads to an overestimation of discrimination or even a false finding of discrimination where there is none. Minorities on average earn less than non-Hispanic whites, thus two individuals of different races with the same annual income tend to have different proportions of transitory income, an insight made by Friedman (1957). An African-American mortgage applicant earning the same income as a white applicant is therefore more likely to experience downward reversion to the mean in future years. To overcome this problem of overestimation, race and ethnicity specific reversion to the mean functions are estimated using PSID income data from 19942004, which relate single year income to the subsequent ten-year income average. When this measure of estimated future income is used instead of current year income, the coefficient for discrimination in the standard loan approval model is reduced for both African-Americans and Hispanics. Applying the same method to home ownership and mortgage holding regressions we find that the dummy variable generally interpreted as discrimination is reduced by two thirds for Hispanics and completely vanishes for African-Americans.
Keywords: G20; G21; J71; 330; Discrimination in Mortgage Loans; Mortgages; Mean Reversion; Hypothek; Ethnische Diskriminierung; Hispano-Amerikaner; Schwarze; USA